Association between MR-proADM concentration and treatment intensity of antihypertensive agents in chronic kidney disease patients with insufficient blood pressure control - Motoshi Iwao (Nature Portfolio, 2021)
Abstract Response to antihypertensive drugs in patients with chronic kidney disease (CKD) has great interindividual variability. Adrenomedullin (ADM) is produced abundantly in hypertension, but clearance is very rapid. Mid-regional proADM (MR-proADM) produced from an ADM precursor is considered a surrogate biomarker for quantification of ADM. We investigated the association of MR-proADM with antihypertensive resistance in CKD patients with poor blood pressure (BP) control. This cross-sectional study analyzed 33 CKD patients with poor BP control defined as failure to achieve target BP despite at least two classes of antihypertensive drugs. Treatment intensity score was calculated to facilitate comparability of antihypertensive regimens across subjects taking different drugs. Plasma MR-proADM concentration was measured using ultra-performance liquid chromatography coupled with tandem mass spectrometry. Plasma MR-proADM concentration correlated with estimated glomerular filtration rate (eGFR) (r =  − 0.777, p < 0.001). Treatment intensity score correlated positively with plasma MR-proADM concentration (r = 0.355, p = 0.043), and the correlation was further enhanced after correction by weight (r = 0.538, p = 0.001). Single and multiple regression analysis identified MR-proADM concentration (p = 0.005) as independently associated with weight-corrected treatment intensity score. MR-proADM may be useful as a biomarker to determine the therapeutic intensity of antihypertensive drugs in CKD patients with poor BP control.